Politics under the influence : vodka and public policy in Putin's Russia - Bailey, Anna L. (Cornell University Press, 2018)
"The first English-language book on Russian alcohol policy in the post-Soviet period; a study of the realities of contemporary Russian policymaking, governance, and cronyism"--